Implementing Lean Manufacturing in Flextronics Brazil, Sorocaba Using Consultants - Muthiyah, Vijayakumar (2011)
Today, numerous companies have a major opportunity to reduce their costs and customer lead time and cycle time through the application of Lean Manufacturing processes. Its roots lie in the manufacturing industry and are strongly influenced by the production system principles originally developed by the lead automotive company called Toyota in Japan. These Lean Manufacturing technologies have been widely utilized and applied by numerous manufacturing companies worldwide. However, not many organizations talk about how the Lean Manufacturing process has a large and long lasting impact on their performance and profits. This research paper focused on behaviours that organizations must exhibit to correctly implement and sustain lean manufacturing practices. The purpose of this case study was to determine how the consultants are implementing the Lean Manufacturing process based on the company, Flextronics which was located in Sorocaba Brazil. This paper also focused on how the business consultants execute organizational change such as “Lean Manufacturing Implementation Process” in the real business world from a corporate training standpoint. Lean Manufacturing fundamentally seeks to remove non-value-added processes from production in order to improve efficiency. Upon completion of this case study, the researcher will be able to define how the manufacturing industry can learn more about the Lean Manufacturing process and not be concerned with the size of a company.